Respect for Seleukid Suzerainty: The Imitative Victory Coinage of the Sistan Ariaspi - Taylor, Lloyd W. H. (KOINON: The International Journal of Classical Numismatic Studies, 2021)
The victory coinage bearing the name Antiochos (SC 226-228), currently attributed to the province of Drangiana during the co-regency of Seleukos and Antiochos, exhibits a progressive deterioration of iconography and epigraphy over the duration of its emission. It has the characteristics of an imitative coinage, struck over a prolonged period, rather than the 14 years of the co-regency. Die study reveals stages of iconographic deterioration, enabling the coinage to be categorized into three groups, each with its own progressively degraded iconography and epigraphy. During its emission a local artistic tradition, possibly reflecting a longstanding Indian influence appears in the iconography of the obverse, and what appears to be an early Brahmi script eventually displaces Greek on the reverse. This is interpreted to reflect contemporary Mauryan cultural and linguistic influences, the result of interaction with adjacent Arachosia. Plausibly, the coinage was struck intermittently in the period c. 281-175 BC by the Ariaspi, the semi-autonomous people of the Sistan depression in Drangiana, who acknowledged Seleukid suzerainty in the choice of coin type and legend.